Inside Back Cover. Issue 5 (11th September 2022) - Unknown
Abstract : Eco‐friendly colloidal core/shell quantum dots are promising building blocks for cost‐effective and high‐efficiency solar energy conversionapplications. In articlenumber eom2.12206, Tong and Wangdeveloped a new type of eco‐friendly CuGaS2 /ZnSe core/shell quantum dots with shell thickness‐tailoredoptoelectronic propertiesto fabricatesolar‐drivenphotoelectrochemical cellforenhancedhydrogen evolutionperformance, demonstrating the great potential of as‐prepared quantum dots infutureenvironment‐friendly solartechnologies. Abstract : Eco‐friendly colloidal core/shell quantum dots are promising building blocks for cost‐effective and high‐efficiency solar energy conversionapplications. In articlenumber eom2.12206, Tong and Wangdeveloped a new type of eco‐friendly CuGaS2 /ZnSe core/shell quantum dots with shell thickness‐tailoredoptoelectronic propertiesto fabricatesolar‐drivenphotoelectrochemical cellforenhancedhydrogen evolutionperformance, demonstrating the great potential of as‐prepared quantum dots infutureenvironment‐friendly solartechnologies.